A Framework for Urban Transport Benchmarking - Henning, Theuns; Essakali, Mohammed Dalil; Oh, Jung Eun (World Bank, Washington, DC, 2013)
This report summarizes the findings of a study aimed at exploring key elements of a benchmarking framework for urban transport. Unlike many industries where benchmarking has proven to be successful and straightforward, the multitude of the actors and interactions involved in urban transport systems may make benchmarking a complex endeavor. It was therefore important to analyze what has been done so far, propose basic benchmarking elements and test them, and identify lessons for a simple and sustainable urban transport benchmarking framework. A major component of this study was to investigate (a) the availability of data for benchmarking and (b) the value of benchmarking on the basis of limited data. The study therefore proposes a benchmarking framework for urban transport, focusing on the performance of public transport. Because the design of a benchmarking framework depends on the objectives sought from it, the study focused on the performance of public transport systems from the policymaker s perspective. The study included pilot application of the proposed framework in five cities from three continents Beijing, Bucharest, Cape Town, Colombo, and Singapore. The pilot application and comparative analysis helped gauge applicability and practicality of the proposed framework.